(untitled) (CIPEEX, 2024)
The transition between adolescence and young adulthood is a potentially conflicting phase, full ofquestions, discoveries and challenges, a dynamic that in its development can result in maturity and resilience, or, as is very common due to numerous risk factors, can trigger mental disorders such as anxiety and depression. The aim of this study is to investigate the prevalence of symptoms of anxiety and depression among young university students and to understand their impact on their well-being. Although the literature includes points about young people and adolescents, the main emphasis is onthe young/adult age group due to the availability of access to this public for data collection, as well as for the enrichment and interpretation of the information obtained, since this population presents convergences and divergences in the expressions generated by the following disorders, which can contribute to understanding the mental health difficulties faced by this category in an emerging phase. The methodology used in this analysis is exploratory field research, with a cross-sectional, observational and quantitative approach.